2020
DOI: 10.1097/md.0000000000020402
|View full text |Cite
|
Sign up to set email alerts
|

Influences of different dose of tirofiban for acute ST elevation myocardial infarction patients underwent percutaneous coronary intervention

Abstract: Tirofiban is widely used in patients with acute ST elevation myocardial infarction (STEMI) underwent percutaneous coronary intervention (PCI). This drug can efficiently improve myocardial perfusion and cardiac function, but its dose still remains controversial. We here investigated the effects of different dose of tirofiban on myocardial reperfusion and heart function in patients with STEMI. A total of 312 STEMI patients who underwent PCI in our hospital from March 2017 to March 2018 were enrolled and randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 32 publications
2
21
0
Order By: Relevance
“…e left ventricular systolic function and diastolic function are related to the LVEF, LVEDD, and LVESD [41]. e study demonstrated that at day 30 after PCI, the LVEF, LVEDD, and LVESD values in the mediumdose group treated with 10 μg/kg tirofiban were superior to those in the control group treated without tirofiban, and the LVEF in the medium-dose group was higher than that in the low-dose group treated with 5 μg/kg tirofiban [42]. We found that there was no significant difference on the LVEDD and LVESD in the PCI + tirofiban group and the PCI group at day 7 after PCI, but the LVEF value was higher in the PCI + tirofiban group compared with the PCI group.…”
Section: Discussionmentioning
confidence: 99%
“…e left ventricular systolic function and diastolic function are related to the LVEF, LVEDD, and LVESD [41]. e study demonstrated that at day 30 after PCI, the LVEF, LVEDD, and LVESD values in the mediumdose group treated with 10 μg/kg tirofiban were superior to those in the control group treated without tirofiban, and the LVEF in the medium-dose group was higher than that in the low-dose group treated with 5 μg/kg tirofiban [42]. We found that there was no significant difference on the LVEDD and LVESD in the PCI + tirofiban group and the PCI group at day 7 after PCI, but the LVEF value was higher in the PCI + tirofiban group compared with the PCI group.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical analyses PASS 15.0 software was used to calculate the sample size. Indicators of myocardial perfusion were noted signi cantly improved in a high-dose treatment group (20 µg/kg) over the medium-dose group (10 µg/kg), while resolution of the Sum-STR two hours after operation was 92.21% in the high-dose treatment group and 74.07% in the medium-dose group [5]. In our study, results in the IC group were expected to be consistent with those of the high-dose group.…”
Section: Follow-upmentioning
confidence: 91%
“…However, the restoration of large-vessel ow does not necessarily equate to recovery of myocardial tissue perfusion and lessening of ischemia-reperfusion injury. Studies demonstrated that serious cardiovascular adverse events, such as cardiac failure, cardiogenic shock, malignant arrhythmia, and sudden cardiac death, appear after PPCI, due to a lack of effective myocardial perfusion and insu cient oxygen supply in the myocardium [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…According to previous literature 23 and the requirements of statistical software, the minimum sample size of low-dose, medium-dose and high-dose groups was 65 cases, 210 cases and 60 cases, respectively. The data were analyzed with SPSS version 19 (IBM, Somers, NY, USA).…”
Section: Methodsmentioning
confidence: 99%